A Potrait of Neo-Sufism in Central Kalimantan (A Study on KH Haderaine HN’s Examination) - Sulaiman Al Kumay (Analisa: Journal of Social Science and Religion, 2015)
TThis article aims to elaborate the ideas of neo-Sufism of KHHaderanie HN, a prominent Sufi scholar in Central Kalimantan. He represents a portrait of Sufism in the contemporary era in Central Kalimantan in particular, and in Indonesia in general. He straightened the correct understanding of Sufism in accordance with the Qur’an and Hadith. This alignment is done because he saw an understanding of Sufism which tends to deviate from the true Sufism. At the same time, he is also a true defender of the ideas of past Sufism that were mostly attacked and slandered, with a straight language in the contemporary context so that it is easy to understand. This defense is his greatest contribution in placing of Sufism as an integral part of trilogy of Islam: īmān, Islām, and  iḥsān.